Macrophage Membrane-Coated Liposomes Delivering Vonoprazan Disrupt Mitochondrial Oxidative Phosphorylation in Diffuse Large B-Cell Lymphoma - Wang W; Wang L; Fan Q; Xu J; Li Y; Xu J; Zhao B; Ge D; Xiong L; Wu Y; Zhu Y; Chen M (International Journal of Nanomedicine)
Weiwei Wang,1,* Lei Wang,2,* Qingqing Fan,3,* Jingyan Xu,1 Yifan Li,4 Jiale Xu,4 Bei Zhao,2 Dan Ge,2 Longying Xiong,2 Yanping Wu,2 Yun Zhu,4,5 Min Chen4 1Department of Hematology, Nanjing Drum Tower Hospital Clinical College of Nanjing University of Chinese Medicine, Nanjing, Jiangsu Province, 21008, People’s Republic of China; 2Department of Gastroenterology, Nanjing Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, Nanjing, Jiangsu Province, 210008, People’s Republic of China; 3Department of Pharmacy, West China Hospital, Sichuan University, Chengdu, 610041, People’s Republic of China; 4Department of Gastroenterology, Nanjing Drum Tower Hospital Clinical College of Nanjing University of Chinese Medicine, Nanjing, Jiangsu Province, 21008, People’s Republic of China; 5Department of Pharmacy, Nanjing Drum Tower Hospital, The Affiliated Hospital of Nanjing University Medical School, Nanjing, 210008, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun Zhu, Email njglyyzhuy@cpu.edu.cn Min Chen, Email croweminchan@nju.edu.cnBackground: A significant proportion of patients fail to respond adequately to the standard R-CHOP regimen for diffuse large B-cell lymphoma (DLBCL). Rapid proliferation requires energy and the interaction between H+ ions and mitochondria suggests that regulating acid secretion in tumor cells may be a therapeutic strategy for DLBCL. This study constructed a macrophage membrane-coated liposomal formulation (MM-Lipid@Vpz) for the targeted delivery of vonoprazan to combat DLBCL, which enables the evasion of the reticuloendothelial system, ensuring enhanced specificity in tumor targeting.Methods: The vonoprazan was delivered by encapsulating liposomes with pre-isolated macrophage membranes, targeted to DLBCL cells and evaluated for changes in cell function. The cellular transcriptome was collected to analyze the mechanism of drug action. An in vivo DLBCL nude mouse subcutaneous tumor model was also established to validate in vitro drug efficacy. In addition, MM-Lipid@Vpz was combined with doxorubicin (Dox) in this study to investigate the effect of action between the two.Results: Lipid@Vpz was prepared by mixing lecithin, cholesterol, DSPE-PEG2000 and vonoprazan at a mass ratio of 100:30:1:10 and dissolving them in anhydrous ethanol. After fusing the macrophage membrane with Lipid@Vpz by extrusion, the particle size increased to 135.37 ± 12.55 nm and the zeta potential changed to − 20.42 ± 1.37 mV. Compared with Lipid@Vpz, MM-Lipid@Vpz significantly increased the intracellular internalization efficiency of vonoprazan by 4.42 times and increased the tumor accumulation in mice by 60.10%. In addition, MM-Lipid@Vpz induced apoptosis in SU-DHL-8 cells at a rate 1.26 times that of Lipid@Vpz and increased the intracellular reactive oxygen species (ROS) level to 1.18 times that of Lipid@Vpz by disrupting mitochondrial oxidative phosphorylation (OXPHOS) and altering mitochondrial morphology. When combined with existing first-line agents such as Dox, MM-Lipid@Vpz manifested synergistic antitumor effects, further augmenting tumor suppression and potentially mitigating drug resistance.Conclusion: Bionic macrophage membrane-encapsulated vonoprazan preparations inhibit DLBCL cellular energy metabolism both in vivo and ex vivo by affecting mitochondrial OXPHOS, which provides data to support the improvement of the prognosis of patients with DLBCL by precise metabolic disruption.Keywords: DLBCL, vonoprazan, macrophage membranes, doxorubicin, oxidative phosphorylation